Application of Foot Massage Therapy with Lavender Oil and Pursed Lip Breathing in Lung Cancer Patients : A Case Report - Safitri, Dania Iva; Pahria, Tuti; Harun, Hasniatisari (Journal of Nursing Care, 2025)
Lung cancer is one of the leading causes of cancer-related deaths worldwide. In advanced stages, patients often experience pain and shortness of breath, which significantly reduce their quality of life. Non-pharmacological interventions such as foot massage with lavender essential oil and pursed lip breathing (PLB) exercises offer potential supportive therapy, but evidence on their effectiveness remains limited. This case study aimed to describe the application of foot massage and PLB techniques in reducing pain and dyspnea in a 64-year-old male diagnosed with stage IVA squamous cell lung carcinoma. The intervention was conducted over six consecutive days. Foot massage was performed using five standard techniques—effleurage, petrissage, friction, tapotement, and vibration—while PLB was practiced for 10 minutes prior to each session. Pain intensity and oxygen saturation were measured using the Numeric Rating Scale (NRS) and pulse oximetry, respectively. The results showed a decrease in pain score from 7 to 3 and an improvement in oxygen saturation from 92% to 96%. The patient also reported improved comfort and the ability to perform light activities with assistance. These findings suggest that the combination of foot massage and PLB may be effective in managing pain and respiratory symptoms in advanced lung cancer. Further research with larger sample sizes and controlled study designs is recommended to confirm these outcomes and support broader clinical use.Keywords: Foot Massage Therapy, Lavender Oil , Lung Cancer, Pain, Pursed Lip Breathing, Shortness of Breath